2022
DOI: 10.1038/s41467-022-30294-8
|View full text |Cite
|
Sign up to set email alerts
|

Rationally engineering santalene synthase to readjust the component ratio of sandalwood oil

Abstract: Plant essential oils (PEOs) are widely used in cosmetic and nutraceutical industries. The component ratios of PEOs determine their qualities. Controlling the component ratios is challenging in construction of PEO biotechnological platforms. Here, we explore the catalytic reaction pathways of both product-promiscuous and product-specific santalene synthases (i.e., SaSSy and SanSyn) by multiscale simulations. F441 of SanSyn is found as a key residue restricting the conformational dynamics of the intermediates, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…9 Recently, SAS was rationally engineered to produce different santalene isomers (e.g., α-santalene and βsantalene). 10 In addition to S. cerevisiae, several other chassis organisms have been engineered for the biosynthesis of αsantalene, such as Escherichia coli, 11 Yarrowia lipolytica, 12 and Nicotiana tabacum. 13 While S. cerevisiae is the preferred cell factory for the biosynthesis of natural products, 14 the methylotrophic yeast Komagataella phaffii (previously known as Pichia pastoris) demonstrates the advantages in expressing heterologous genes to high levels.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, SAS was rationally engineered to produce different santalene isomers (e.g., α-santalene and βsantalene). 10 In addition to S. cerevisiae, several other chassis organisms have been engineered for the biosynthesis of αsantalene, such as Escherichia coli, 11 Yarrowia lipolytica, 12 and Nicotiana tabacum. 13 While S. cerevisiae is the preferred cell factory for the biosynthesis of natural products, 14 the methylotrophic yeast Komagataella phaffii (previously known as Pichia pastoris) demonstrates the advantages in expressing heterologous genes to high levels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…cerevisiae for the production of santalene and santalol, whose titer reached as high as 0.3 and 1.3 g/L, respectively, using fed-batch fermentation . Recently, SAS was rationally engineered to produce different santalene isomers (e.g., α-santalene and β-santalene) . In addition to S.…”
Section: Introductionmentioning
confidence: 99%
“…For catalysis by the diterpene synthase CotB2, the free energy profiles of the reaction cascade in the presence or absence of CotB2 are similar, which is probably attributed to the balanced interaction between the enzyme and carbocationic intermediates . In our own previous work, we proposed that three factors determine catalytic promiscuity versus specificity: the substrate folding mode, the presence of key active site residues, and the flexibility of intermediates that is mainly a consequence of the available space in the active site. , Thus, the production of 1 , 2 , or 3 in the variants of BcBOT2, DbPROS, and CLM1, respectively, and their promiscuity observed in several cases provide new insights that may provoke future investigations of these phenomena.…”
Section: Discussionmentioning
confidence: 95%
“…Wu et al explored the reaction pathways of both santalene synthases (SaSSy and SanSyn) using QM/MM MD simulation. 114 In the early stage of research, much attention was placed on computation and experiment on SaSSy in order to reduce the yield of the side product exo-α-bergamotene. Unfortunately, all redesigned mutants were ineffective or resulted in an increase in undesired side products.…”
Section: Readjust the Product Ratio Of Santalenementioning
confidence: 99%
“…In recent years, many QM/MM aided enzyme function reshaping studies have been performed on terpene synthases, especially new function reshaping. Duan et al identified several new functional OSCs from the medicinal plant Iris tectorum , including ItOSC2, a rare multifunctional α-amyrin synthase. Wu et al began with QM/MM MD modeling on ItOSC2 to figure out the two pathways: one common β-amyrin pathway and one particular α-amyrin pathway.…”
Section: Qm/mm Modeling Aided Enzyme Function Reshapingmentioning
confidence: 99%